Novel theoretical modeling of quadruple Pass Erbium Doped Fiber Amplifier - Naji, Ahmed Wathik; Mohammed, M. A.; Ahmed, Belal; Harun, S.W.; Mahdi, M.A. (2010)
In this paper, a novel theoretical model of an Erbium Doped Fiber Amplifier (EDFA) configured in Quadruple Pass Dual Stage (QPDS) amplification which is incorporated with Tunable band pass filters (TBFs) is proposed. Amplified Spontaneous Emission (ASE) is filtered-out in mid-section to ensure efficient amplification of the signal as it propagates along the fiber. The two stages were pumped by laser diodes operating at 980 nm with 10 mW and 220 mW, respectivitely. Also, design parameters of EDFA are optimized using the numerical simulation of EDFA rate equation model in order to optimize the performance of the EDFA. High gain of 61 dB is achieved for -50 dBm signal power at 1550 nm input signal wavelength. The developed model can be used to design and analyze the performance of the EDF and to enhance the optical fiber communication system performance.